The FRBNY Staff Underlying Inflation Gauge: UIG - Marlene Amstad; Simon Potter; Robert Rich (Federal Reserve Bank of New York, 2014)
Monetary policymakers and long-term investors would benefit greatly from a measure of underlying inflation that uses all relevant information, is available in real time, and forecasts inflation better than traditional underlying inflation measures such as core inflation measures. This paper presents the 'FRBNY Staff Underlying Inflation Gauge (UIG)' for CPI and PCE. Using a dynamic factor model approach, the UIG is derived from a broad data set that extends beyond price series to include a wide range of nominal, real, and financial variables. It also considers the specific and time-varying persistence of individual subcomponents of an inflation series. An attractive feature of the UIG is that it can be updated on a daily basis, which allows for a close monitoring of changes in underlying inflation. This capability can be very useful when large and sudden economic fluctuations occur, as at the end of 2008. In addition, the UIG displays greater forecast accuracy than traditional measures of core inflation.
Keywords: C13; C33; C43; E31; E37; 330; Inflation; Dynamic Factor Models; Core Inflation; Monetary Policy; Forecasting